2023
DOI: 10.1111/nph.18782
|View full text |Cite
|
Sign up to set email alerts
|

Interchromosomal linkage disequilibrium and linked fitness cost loci associated with selection for herbicide resistance

Abstract: Summary The adaptation of weeds to herbicide is both a significant problem in agriculture and a model of rapid adaptation. However, significant gaps remain in our knowledge of resistance controlled by many loci and the evolutionary factors that influence the maintenance of resistance. Here, using herbicide‐resistant populations of the common morning glory (Ipomoea purpurea), we perform a multilevel analysis of the genome and transcriptome to uncover putative loci involved in nontarget‐site herbicide resistanc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 107 publications
0
15
0
Order By: Relevance
“…The fact that the flowering-time genes gave nearly identical signals with regard to their association with flowering time suggests, as displayed in Figure 2b, that SNPs at flowering-time genes harbor similar allele frequencies. These similar allele frequencies indicate that some flowering-time genes might be co-selected (polygenic selection) and remain in strong linkage disequilibrium despite the large physical distances that separate them (Zan and Carlborg 2019; Gupta et al 2023).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The fact that the flowering-time genes gave nearly identical signals with regard to their association with flowering time suggests, as displayed in Figure 2b, that SNPs at flowering-time genes harbor similar allele frequencies. These similar allele frequencies indicate that some flowering-time genes might be co-selected (polygenic selection) and remain in strong linkage disequilibrium despite the large physical distances that separate them (Zan and Carlborg 2019; Gupta et al 2023).…”
Section: Resultsmentioning
confidence: 93%
“…Third, we highlighted a striking pattern of long-range linkage disequilibrium (LD), both intra- and inter-chromosomal, among 14 flowering-time genes associated with flowering time variation under greenhouse conditions (Figure 4). Polygenic selection is expected to result in LD between regions under selection (Gupta et al 2023; Yeaman et al 2016; 2018) but only few cases have been reported so far in plants and animals (Hohenlohe et al 2012; Yeaman et al 2016; Gupta et al 2023; Park 2019). In A. thaliana, Zan and Carlborg (2019) also identified long-range LD among four clusters of flowering-time genes.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of CPR genes and copy number was searched in several important weed species. The genomes of Alopecurus myosuroides (Cai et al ., 2023), Chenopodium formosanum (Jarvis et al ., 2022), Bassia scoparia (Hall et al ., 2023), Eleusine indica (Zhang et al ., 2023), Bromus tectorum (Revolinski et al ., 2023), Echinochloa crus-galli (Wu et al ., 2022), E. oryzicola (Wu et al ., 2022), E. colona (Wu et al ., 2022), Ipomoea purpurea (Gupta et al ., 2023) , Poa annua (Robbins et al ., 2023), and Conyza canadensis (Laforest et al ., 2020) were accessible through WeedPedia (https://weedpedia.weedgenomics.org) (Montgomery et al ., 2023). CPRs were identified with a blast search using ATR1 (AT4G24520) or ATR2 (AT4G30210) against the genomes or utilized the InterPro ID for NADPH-cytochrome P450 reductase (IPR023208).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, epigenetic modifications have been hypothesized to play a role in NTSR, with much remaining to be explored [126][127][128]. Untargeted approaches such as genome-wide association, selective sweep scans, linkage mapping, RNA-sequencing, and metabolomic profiling have proven helpful to complement more specific biochemical-and chemocharacterization studies towards the elucidation of NTSR mechanisms as well as their regulation and evolution [60,[129][130][131][132][133][134][135][136]. Due to their complexity and importance, the IWGC has begun addressing this subject by manually curating the annotation of NTSR genes and developing a standard nomenclature for the gene families often involved in NTSR.…”
Section: Genetic Basis Of Herbicide Resistancementioning
confidence: 99%